Prasangka Terhadap Etnis Tionghoa: Peran Etnosentrisme dan Orientasi Dominasi Sosial - Prasetya, Eva Natalia; Tondok, Marselius Sampe (Jurnal Psikologi Perseptual, 2023)
This Ethnic diversity in Indonesia has led to social prejudice, especially towards ethnic minorities, one of which is the Chinese Indonesian. Various factors that influence social prejudice include ethnocentrism and social dominance orientation. This study aimed to determine the role of ethnocentrism and social dominance orientation among students of native ethnic groups toward prejudice against Chinese Indonesians. This study used a cross-sectional quantitative survey design. Participants in this research were undergraduate students from several universities in Indonesia who were selected using an accidental sampling technique. Multiple regression analysis was employed as a data analysis method for testing the hypothesis. The results of the research showed that ethnocentrism and social domination orientation simultaneously or partially played a significant role in explaining ethnic prejudice. Ethnocentrism and social domination orientation have a role of 17.2% in explaining the prejudice against Chinese Ethnicity. Furthermore, ethnocentrism (14.4%) has a greater influence than social dominance orientation (2.7%) in explaining prejudice against ethnic Chinese. The findings and the implications of this study are discussed in more detail. Keberagaman etnis di Indonesia telah menimbulkan prasangka sosial, khususnya terhadap etnis minoritas, salah satunya adalah Tionghoa. Berbagai faktor yang mempengaruhi prasangka sosial antara lain etnosentrisme dan orientasi dominasi sosial. Penelitian ini bertujuan mengetahui peran antara etnosentrisme dan orientasi dominasi sosial di antara mahasiswa etnis masyarakat lokal dan prasangka terhadap Etnis Tionghoa. Penelitian ini menggunakan desain survei kuantitatif cross-sectional. Partisipan dalam penelitian ini adalah mahasiswa S1 dari beberapa perguruan tinggi di Indonesia yang dipilih melalui teknik accidental sampling. Teknik analisis data untuk menguji hipotesis menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa etnosentrisme dan orientasi dominasi sosial secara bersama-sama maupun parsial berperan secara signifikan dalam menjelaskan prasangka etnis. Etnosentrisme dan orientasi dominasi sosial memiliki peran sebesar 17,2% dalam menjelaskan prasangka terhadap Etnis Tionghoa. Selanjutnya, etnosentrisme (14,5%) memiliki pengaruh yang lebih besar daripada orientasi dominasi sosial (2,7%) dalam menjelaskan prasangka terhadap etnis Tionghoa. Temuan dan implikasi dari penelitian ini dibahas lebih lanjut.